2017
DOI: 10.3390/molecules22081240
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Uptake of Fe3O4 Nanoparticles by Intestinal Epithelial Cells in a State of Inflammation

Abstract: Fe3O4 nanoparticles (Fe3O4 NPs) have been used for medical and drug applications, although the mechanisms of cellular uptake and transport need to be further evaluated under inflammatory conditions. In the present study, we investigated the uptake of Fe3O4 NPs (20, 50, 100, and 200 nm) by intestinal epithelial cells under inflammatory conditions via the light scattering of flow cytometry and inductively coupled plasma mass spectrometry (ICP-MS) techniques. The results of the correlation analysis indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Zhou et al, previously reported enhanced uptake of 200 nm Fe 3 O 4 NPs by clathrin-mediated mechanisms in an inflamed caco-2 cell model. Inflamed cells were found to express three times as much clathrin as their healthy counterparts [ 31 ]. It is known in IBD that inflammatory cytokines such as IL-1β, TNF and IFN-γ cause dysregulation of endocytic mechanisms leading to enhanced uptake of tight junction proteins and bacteria which contribute to barrier disruption and disease pathogenesis [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al, previously reported enhanced uptake of 200 nm Fe 3 O 4 NPs by clathrin-mediated mechanisms in an inflamed caco-2 cell model. Inflamed cells were found to express three times as much clathrin as their healthy counterparts [ 31 ]. It is known in IBD that inflammatory cytokines such as IL-1β, TNF and IFN-γ cause dysregulation of endocytic mechanisms leading to enhanced uptake of tight junction proteins and bacteria which contribute to barrier disruption and disease pathogenesis [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that the uptake and transportation ratios of nanoparticles by IEC in a state of inflammation are enhanced compared with the control [ 41 ]. This phenomenon has clear relevance for the uptake of phages by normal and inflamed IEC.…”
Section: Iec and Immunitymentioning
confidence: 99%
“…The internalization of nanoparticles in cells is influenced by their physicochemical properties and the cells’ microenvironment (Fig. 1 ) (Li and Monteiro-Riviere 2016 ; Brkić Ahmed et al 2017 ; Zhou et al 2017 ; Dreifuss et al 2018 ). The main characteristics involved are size, shape, surface charge, surface functional groups, and hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) can be uptaken across the plasma membrane by various mechanisms, from passive diffusion to active transport. The endocytic and non-endocytic pathways are the most common among these mechanisms (Kettler et al 2014 ; Zhang et al 2016 ; Brkić Ahmed 2017 ; Zhou et al 2017 ; Dreifuss et al 2018 ). Diffusion is the movement of molecules from more to less concentrated gradients, and usually occurs for small, hydrophobic, and uncharged molecules.…”
Section: Introductionmentioning
confidence: 99%